HUBUNGAN FAKTOR PEKERJAAN DAN FAKTOR INDIVIDU TERHADAP KELUHAN MUSKULOSKELETAL PADA PEKERJA PEMBUAT TUGU PARAS TARO - Nia Sistari, Ni Luh Made; Ady Wirawan, I Md (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 2 (2023): Agustus 2023, 2023)
ABSTRACT Informal sector is an employment sector that does not yet have a good occupational health and safety implementation. Based on occupational and individual factors, workers in the informal craft sector in Bali, especially workers who make the tugu Paras Taro are at risk of musculoskeletal complaints. This study aims to determine the risk factors for musculoskeletal complaints to tugu Paras Taro workers. The design of this research is analytic observational with cross sectional which was conducted from January to June 2022 on 97 respondents. Banjar Taro Kaja was chosen as the research site by purposive sampling, while the sample was selected by convenience sampling. The data collection instruments used were the Nordic Body Map questionnaire, the BRIEF Survey assessment, and metlin tape. Data were analyzed using chi square test and logistic regression. The results showed that there were 75 respondents (77.32%) who had musculoskeletal complaints. The results of data analysis showed that occupational factors had no relationship with musculoskeletal complaints (p>0.05). While on individual factors, age is the associated with musculoskeletal complaints (p<0.05) with a risk 3.44 times to increase the risk for workers with aged  ?30 years old. The workers with aged  ?30 years old expected not to take on a job with a heavy load. Keyword : musculoskeletal complaints, informal sector, BRIEF Survey, Nordic Body Map   ABSTRAK Sektor informal merupakan sektor pekerjaan yang belum memiliki penerapan K3 yang baik. Berdasarkan faktor pekerjaan dan faktor individu, pekerja pada sektor kerajinan informal di Bali khususnya pekerja pembuat tugu Paras Taro memiliki risiko keluhan muskuloskeletal. Penelitian ini bertujuan untuk mengetahui faktor risiko keluhan muskuloskeletal terhadap pekerja pembuat tugu Paras Taro. Desain penelitian ini adalah observasional analitik dengan pendekatan cross sectional yang dilakukan pada bulan Januari sampai bulan Juni 2022 pada 97 responden. Banjar Taro Kaja dipilih sebagai tempat penelitian dengan purposive sampling , sementara sampel dipilih dengan convenience sampling . Instrument pengumpulan data yang digunakan adalah kuesioner Nordic Body Map, lembar penilaian BRIEF Survey, dan pita metlin. Data dianalisis menggunakan uji chi square dan regresi logistik. Hasil penelitian menunjukkan terdapat 75 responden (77,32%) yang mengalami keluhan muskuloskeletal. Hasil analisis data menunjukkan bahwa faktor pekerjaan tidak memiliki hubungan dengan dengan keluhan muskuloskeletal (p>0,05). Sementara pada faktor individu, usia dan keluhan muskuloskeletal dinyatakan memiliki hubungan dengan risiko 3,44 kali lebih besar pada pekerja berusia ?30 tahun (p<0,05). Pekerja berusia ?30 tahun diharapkan tidak mengambil pekerjaan dengan beban terlalu berat. Kata Kunci: keluhan muskuloskeletal, sektor informal, BRIEF Survey, Nordic Body Map